Communication related to medication incidents—A concept analysis and literature review. Issue 2 (15th November 2021) - Syyrilä, Tiina; Vehviläinen‐Julkunen, Katri; Manias, Elizabeth; Bucknall, Tracey; Härkänen, Marja
Abstract: Aims: (1) To identify and analyse the conceptual framework and operationalise the concept of communication issues related to medication incidents in hospital to facilitate the development of a future tool for measuring frequencies of the communication issues. (2) To determine how the concept is distinct from related concepts. Design: Concept analysis. Data sources: Twenty‐three articles from seven scientific databases covering the years 2010–2020 and two official documents. Methods: Walker and Avant's concept analysis method was used. That was started by a systematised literature review on 2 November 2020 using specified criteria. Two authors evaluated articles' quality by Joanna Brigg's Institute's criteria. Literature review results were analysed deductive‐inductively; conceptual framework was developed and concept defined presenting case scenarios. EQUATOR's standards were used in study reporting. Results: A conceptual framework and the concept of 'communication related to medication incidents in hospitals' were defined, comprising six main attribute categories: (1) communication dyads involved in communication, (2) patients' or professionals' individual issues, (3) institutional, (4) contextual and process issues, (5) communication concerning medication prescriptions and (6) qualitative characteristics of communication. The categories consisted of 128 quantitatively measurable and 10 qualitative attributes describing communication issues. The concept is distinct from related concepts by collating fragmented communication issues into the same concept. Conclusion: The 128‐item conceptual framework and the concept of communication related to medication incidents in hospitals were defined, as there was not one. The concept assembled parts of previous theories and fragmented information to one entity. The concept needs further condensing and validation to develop a tool for measuring communication issues. Impact on medication safety: The conceptual framework can be used in practice and education as indicative rationale for reflection of current communication issues. The concept contributes to research by providing necessary grounding for tool development for measuring communication factors relating medication incidents.